2023
DOI: 10.3389/fnut.2023.1214875
|View full text |Cite
|
Sign up to set email alerts
|

Associations between composite dietary antioxidant index and estimated 10-year atherosclerotic cardiovascular disease risk among U.S. adults

Jia Zhang,
Xueqin Lu,
Ruifeng Wu
et al.

Abstract: BackgroundAtherosclerotic cardiovascular disease (ASCVD) remains the leading cause of death and disability both in U.S. and worldwide. Antioxidants have been proved critical in mitigating the development of atherosclerosis. This study aimed to investigate the associations between composite dietary antioxidant index (CDAI) and estimated 10-year ASCVD risk among U.S. adults.MethodsData extracted from the National Health and Nutrition Examination Survey were analyzed. A total of 10,984 adults aged 18 years and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…This study also found that the prevalence of hypertension, diabetes mellitus, and coronary heart disease decreased progressively with increasing CDAI. Previous analyses of the NHANES database found that the prevalence of hypertension, coronary heart disease, and diabetes mellitus were negatively correlated with CDAI ( 18 , 23 , 40 ), which is consistent with our findings. Control variables such as energy, carbohydrates, total fat, and cholesterol, which may affect the results of the study, were added to the previous ones.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study also found that the prevalence of hypertension, diabetes mellitus, and coronary heart disease decreased progressively with increasing CDAI. Previous analyses of the NHANES database found that the prevalence of hypertension, coronary heart disease, and diabetes mellitus were negatively correlated with CDAI ( 18 , 23 , 40 ), which is consistent with our findings. Control variables such as energy, carbohydrates, total fat, and cholesterol, which may affect the results of the study, were added to the previous ones.…”
Section: Discussionsupporting
confidence: 93%
“…CDAI was proposed by Wright et al ( 21 ) as a composite score reflecting antioxidant capacity of one’s diet, which includes vitamins A, C, and E, zinc, selenium, and carotenoids. Previous studies have found that CDAI improves heart failure, hypertension, depression, and atherosclerotic cardiovascular disease and reduces the risk of morbidity ( 18 , 22–24 ). However, there are no studies on the relationship between CDAI and hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Therefore, a balanced dietary pattern, such as the Mediterranean diet, which emphasizes the consumption of vegetables, fruits, fish, whole grains, legumes, and olive oil, offers the body an optimal balance to maintain antioxidative capacity, reducing the risk of cardiovascular diseases. 29 31 Several studies have shown that an antioxidant-rich dietary pattern can lower the risk of ASCVD, 32 34 which aligns with our research findings.…”
Section: Discussionsupporting
confidence: 91%
“…18,37–40 The CDAI score is derived from a limited set of six dietary nutrients, specifically vitamins A, C, and E, along with manganese, selenium, and zinc, all of which possess antioxidant properties. 41 However, it should be noted that our diet not only provides us with antioxidant nutrients but also pro-oxidant ones. DOBS not only encompasses a greater abundance of 14 antioxidant nutrients in total but also incorporates 2 pro-oxidant nutrients, making it the sole scoring system that comprehensively evaluates both anti- and pro-oxidative exposures.…”
Section: Discussionmentioning
confidence: 99%